Fatal judgment eaudiobook - Hannon, Irene (Guardians of Justice, 2011)
RITA Award winner Irene Hannon has also won the Holt Medallion and the Daphne du Maurier Award for her romantic suspense. U.S. Marshal Jake Taylor loathes guarding federal judge Liz Michaels. How can he protect the coldhearted workaholic who drove her late husband, Jake's best friend, to suicide? But as he gets to know Liz better, his heart-and her life-are soon in danger. "Hannon is a master at character development."-Library Journal